First report of probe based confocal laser endomicroscopy during medical thoracoscopy. (February 2019) - Bonhomme, O.; Duysinx, B.; Heinen, V.; Detrembleur, N.; Corhay, J.-L.; Louis, R.
Abstract: Probe based confocal laser endomicroscopy (pCLE) is a new optical endoscopic technique, generating fluorescent light emission from the tissue of interest and allowing in vivo live imaging at a cellular level ("optical biopsies"). To the best of our knowledge, this article is the first to present pCLE images during medical thoracoscopy. We present here 3 different patients referred for various health problems. A precise description of pleural cavity pCLE images after intravenous fluorescein injection (a fluorophore) together with corresponding macroscopical and histological studies is performed. This led to the diagnosis of normal pleura in one case, carcinomatous pleuritis in another case and a malignant mesothelioma in the third case. We believe that optical biopsies could help clinicians to make an early diagnosis, thereby allowing rapid therapeutic intervention (talc pleurodesis for example). Furthermore, it could help to guide biopsies when affected zones are not obvious to macroscopic examination. In a near future, new fluorophores could be developed to stain some pathophysiological processes, therapeutic targets, or enzymes activities bringing new insights in endoscopic pleural disease work-up. Highlights: Probe based confocal laser endomicroscopy (pCLE) is a new optical endoscopic technique. pCLE allows in vivo live imaging at a cellular level ("optical biopsies"). We present pictures of pCLE during medical thoracoscopy and a direct comparison between normal pleura and pleural carcinomatosis. Our work shows a clear distinction between normal pleura and pleural carcinomatosis with pCLE.